THE SCIENTIFIC SCHOOL OF THE ACADEMICIAN G. M. ROMANTSEV: THE HISTORY AND PROSPECTS OF DEVELOPMENT - N. V. Ronzhina; A. V. Efanov (Образование и наука)
Introduction. The scientific schools serve as engines of development of science and the training centers for scientists. At the same time, the identity of the founder and head of the scientific school is of great importance; this person has to have unique theoretical thinking, talent and the researcher’s intuition, to be purposeful, responsible for generation of the ideas and personally interested in the development of current scientific problems, as well as to have distinctive managerial and pedagogical qualities.The aim of this article is to analyse the establishment and “evolution” of the scientific school of G. M. Romantsev, the Academician of the Russian Academy of Education; to identify the prospects for the main directions of the school development.Methodology and research methods. The study was based on the hermeneutic method of interpretation and understanding of scientific texts; general scientific methods of analysis, synthesis, comparison, generalization and interpretation of available scientific heritage were applied. Results and scientific novelty. The authors of the present publication have made an attempt to comprehend the content of scholarly writings by G. M. Romantsev and his followers within the framework of the scientific school; a theoretical model of professional pedagogical education in Russia was designed by them. It was found out that most of the research publications are interdisciplinary, often conducted at the intersection of Pedagogy, Psychology, Philosophy, Law and Economics; research and practice nature of most of the studies was defined: theoretical studies are traditionally accompanied by innovative experimental activity. The place of Vocational Pedagogy in the system of pedagogical sciences was proved; its role as theoretical and methodological foundations of vocational-pedagogical education was highlighted as well. The key theoretical and methodological premises of this type of education are formulated; its logical processes and vectors for further development are denoted. Scientific achievements of the scholars of G. M. Romantsev’s school in the field of the higher vocational education are presented; possible ways of advancement of vocational training for workers and handicraftsmen in Russia are presented.Practical significance. The output of the work undertaken by the representatives of the scientific school of G. M. Romantsev continue to be the basis for correction and development of education and vocational standards, the conceptual framework, regulatory background of vocational education, including legal support for occupational guidance among young people. Continued innovative activity of the research team and application in practice of the outcomes obtained will enable to narrow the gap between the theory and practice of vocational education, to enhance the competitiveness of the Russian higher school, and to meet the demands from the manufacturing sector and economy for qualified specialists. Furthermore, the research outcomes can provide substantial assistance to design the modern structure of the pedagogical scientific research organization and build an effective process management workflow.